Opening the red budget box: Nonlinear effects of a tax shock in the UK - Valentina Colombo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
This paper studies the real effects of an exogenous UK tax change in recessions and expansions. The tax shock is identified via the measure proposed by Cloyne (2013). Combining local projection techniques (Jordà, 2005) with smooth transition regressions (Granger and Teräsvirta, 1994), tax policy shock is found to affect UK macroeconomic variables depending on the phase of the business cycle the economy is when tax shock occurs. An exogenous tax cut in recessions triggers a large, persistent, positive, and statistically significant reaction in output, consumption, investment, exports, imports, and government consumption. The results suggest that the output tax multiplier is positive and above one (in absolute value) in recessions but not in expansions. The size and the sign of responses of a number of macroeconomic variables are also found to be state-contingent.
Keywords: E32; E62; H20; 330; Fiscal shocks; tax multipliers; business cycle; local projections